2023
DOI: 10.14423/smj.0000000000001519
|View full text |Cite
|
Sign up to set email alerts
|

Remdesivir-Induced Bradycardia

Abstract: Remdesivir, a viral RNA-dependent RNA polymerase inhibitor, found extensive use in coronavirus disease 2019-infected patients because it curbs the viral load expansion. Among patients hospitalized as a result of lower respiratory tract infection, remdesivir proved to improve recovery time; however, remdesivir also can induce significant cytotoxic effects on cardiac myocytes. In this narrative review, we discuss the pathophysiological mechanism of remdesivir-induced bradycardia and diagnostic and management str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
(34 reference statements)
0
0
0
Order By: Relevance
“…In the present study, the mean age in the group with complications was significantly higher than the group without complications. These results support the findings of previous research that demonstrated an increased prevalence of bradycardia [28] and other cardiac complications [26,29] with Remdesivir in older persons [22]. Older patients who develop cardiac events linked to Remdesivir may have age-related cardiovascular abnormalities, especially in the conduction system [30].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In the present study, the mean age in the group with complications was significantly higher than the group without complications. These results support the findings of previous research that demonstrated an increased prevalence of bradycardia [28] and other cardiac complications [26,29] with Remdesivir in older persons [22]. Older patients who develop cardiac events linked to Remdesivir may have age-related cardiovascular abnormalities, especially in the conduction system [30].…”
Section: Discussionsupporting
confidence: 90%
“…In one observational research with over 6500 COVID-19 patient reports, Remdesivir caused bradycardia as the most common cardiac adverse effect [21]. Remdesivir-induced bradycardia most likely results from sinus node and mitochondrial malfunction [22]. Remdesivir, as an inhibitor of viral RNA polymerases, has antiviral properties, but it also interacts with the human mitochondrial RNA polymerase, inhibiting it and resulting in mitochondrial malfunction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…107 Entre los efectos secundarios más comunes del Remdesivir, se encuentran aquellos en la esfera cardiovascular, 108 siendo la bradicardia el más frecuente, aunque también puede presentarse hipotensión, arritmias tipo fibrilación auricular, prolongación del intervalo QT, ensanchamiento del complejo QRS, Torsade de pointes. 108,109 Comentarios: La aprobación del Remdesivir a pesar de ser útil en circunstancias determinadas, conllevó a la sobreutilización del medicamento. 59 La evidencia sobre su uso aún permanece limitada.…”
Section: Colchicinaunclassified
“…In recent research, there has been considerable interest in investigating the association between remdesivir treatment and the occurrence of bradycardia [8]. Although remdesivir has shown efficacy in treating COVID-19, it is crucial to explore its potential cardiovascular effects, identify risk factors that may result in bradycardia, and gain a deeper understanding of the underlying mechanism.…”
Section: Introductionmentioning
confidence: 99%